Human Resource Adaptive Competence in Digital Disruption: A Humanistic Phenomenological Exploration - Rince Tambunan; Ayuningtyas Putri Mumpuni Halim Asy'Ary; Andi M Budihard; Asraf (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Digital transformation has shifted the paradigm of human resource management from a technical approach to a more reflective and humanistic approach. This study aims to explore human resource   adaptive competency in facing digital disruption through a phenomenological approach. This study was designed using a qualitative approach with an exploratory design to understand the phenomenon of adaptive competency from the perspective of human resource actors in the business sector. This study also involved five key informants from the business sector who were selected purposively. Data were collected through in-depth interviews and analyzed using thematic techniques. The results of the study identified reflective, emotional, and social dimensions as the foundation of adaptive competency, such as reflective practices, a safe culture for learning, cross-generational collaboration, and humility to continue learning. This study enriches the human resource   management literature by offering an adaptive model based on humanistic values that can be applied in various organizational sectors. Its practical implications include the design of human resource development programs that are more oriented towards meaning, resilience, and collaboration. This study provides a conceptual basis for the development of sustainable human resource   strategies in the digital era.